IMPROVING STUDENTS’ READING COMPREHENSION BY USING COLLABORATIVE STRATEGIC READING (CSR) AT TENTH GRADE OF STUDENTS SMAS SHALAHUDDIIN AL-MUNAWWARAH - Esarni, Esarni (Faculty of Tarbiyah nad Teacher Training, 2022)
This research aimed to find out the improving of the students’ reading comprehension by using collaborative strategic reading. This research was conducted by using Classroom Action Research (CAR). The subject of this research was X-C grade of SMAS ShalahuddiinAl-Munawwarah in 2020/2021 academic year and consisted of 28 students. The objective of this research was to improve students’ reading comprehension by using Collaborative Strategic Reading (CSR) at tenth grade of SMAS Shalahuddiin Al- Munawwarah. This research was conducted in two cycles and each cycle consists of planning, acting, observing, and reflecting. The techniques of analysis data were quantitative and qualitative data. The quantitative data were taken from tests, the tests consist of pre-test and post-test. While the qualitative data were taken from observation, interview, diary notes, and documentation. The result of the data analysis showed that there was an improvement in the students’ reading comprehension after implementing Collaboative Strategic Reading. In the pre-test the students mean was 57 and the students who passed the KKM were 4 students of 28 students or 14%. In the post-test I the students mean was 72 and the students who passed KKM were 13 students of 28 students or 46%. And in the post-test II the students mean was 83 and the students who passed KKM were 23 students of 28 students or 82%. And based on the observation sheet, interview, diary notes and documentation, the students were active and enjoy in participation and responses during the teaching-learning process. In the other words, the students’ reading comprehension was improved by using Collaborative Strategic Reading (CSR).